(untitled) (International Journal of Physiotherapy, 2015)
Back ground: Myofascial trigger point (MTPt) can be defined as a hyperirritable spot in skeletal muscle that is associated with a hypersensitive palpable nodule in a taut band. MTPt is associated with pain on compression, the pain is typically of a referred type. MTPt symptoms, cause severe discomfort and inability to work. The pain is aggravated with activity or stress. Untreated, chronic cases might lead to symptoms like depression, fatigue and behavioural disturbances. The objective of the study is to examine the effectiveness of MET on pain with VAS and cervical ROM with inch tape method in patients with myofascial pain in upper trapezius. Methods: participants were randomized into intervention group (n =15) and control group (n = 15).The intervention group was given muscle energy technique, ischemic compression and ultrasound. The control group was given only ischemic compression and ultrasound. Ultrasound 1 MHz continuous mode, intensity 1.5W/cm2 for 5 minutes. Home exercises taught to both the groups. This program designed for daily for 1 week. Outcome measures: Pain-VAS, ROM-Inch tape method (cervical lateral flexion). Results: values within the groups were compared by using paired `t` test. According to obtained values, the pre & posttest values of pain and ROM had an significant effect on p-values 0.00 in experimental group. The difference between the pretest and posttest scores of 95% confidence intervals for each outcome variable was reported. Conclusion: After 1 week of intervention protocol, the present study concludes that MET has significant improvement in pain, ROM in intervention group.